(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
Orthodontic aligner therapy is gaining rapid popularity among the potential orthodontic patients as well as general practitioners. The purpose of this study was to evaluate the knowledge and awareness on clear aligner therapy among undergraduate dental students of the Faculty of Dentistry, University of Benin, Benin City, Nigeria. The study population consisted of eighteen 600 level (Final year) students, twenty two 500 level students and sixteen 400 level students, giving a total population of 63.The study instrument was a self-administered questionnaire. Data was computed and analyzed using SPSS version 21.0. Statistical significance was set at P<0.05.63 respondents consisted the study population. The minimum age was 20 years, maximum age was 35 years, and the mean age was 24.73±2.63 years. Majority of the respondents knew about clear aligners. The 500 level students had a higher population of knowledge on clear aligners (95.6%), and the female population had a higher knowledge on clear aligners (92.3%), and most of them got their information from Dentists. It is necessary to increase the awareness about clear aligners at the undergraduate level, as well as a basic idea about which cases are ideal for treatment with aligners.